Carbon footprint assessment of the construction materials and energy usage of KICT building IIUM - Bah, Mamadou Lamarana (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2021)
The increasing of carbon emissions in our atmosphere is becoming an environmental issue due to climate change and global warming. The effect of all this additional carbon dioxide in the atmosphere is that the global temperature of the planet is increasing, including global warming, leading to unpredictable daily climate changes such as floods, hurricanes, heatwaves, and droughts. Global warming is the primary concern in terms of environmental impact on the climate and geography of our planet. CO2 is responsible for the increase in temperature and much research has been done on how we can reduce the effect of CO2 on the environment. The construction industry is one of the biggest carbon dioxide emitter's activities in the world. In the meantime, the study shows that the amount of carbon emission is higher compared to transportation and industry. In fact, buildings are responsible for more than one-third of total energy consumption and related GHGs emissions in society, in both developed and developing countries. On the other hand, statistics show that in Malaysia, buildings account for about 20 % of GHG production, which comes in third place after transport 27 % and industries 21 %. In 2017, Malaysia ranks 25th in the world in terms of carbon emissions, with 255 MtCO2 of the 36153 MtCO2 world total emissions. In order to minimize the increase in carbon emissions from the construction of the building, several studies have identified some of the effective carbon assessment tools for construction projects such as the Inventory of Carbon & Energy (ICE) developed in the UK, but it is lack of implementation in Malaysia. The Green Building Index (GBI), developed by professional associations. Malaysian government, regarding to sustainability and green construction issues, has also implemented several green agencies such as Ministry of Energy, Technology and Water, GreenTech Malaysia, Green Technology Council, Malaysia Green Building Council and Construction Industry Development Board (CIDB) to assist construction stakeholders in reducing carbon emissions and the impact of buildings on the environment. This thesis presents an analysis of carbon emissions from an office building (KICT building) to identify and quantify the main sources of carbon emissions and energy consumption of the project and proposes environmentally friendly materials to replace conventional building materials to achieve the implementation of sustainability in Malaysia. In addition, the calculations has shown that the values obtain for electricity consumption is 38,191.4 tons CO2 for only twelve (12) months of operation, whereas construction materials give values of 8,262.4 tons CO2, with the difference of 29,929 tons CO2, which represent in term of percentage 82.2 % and 17.8 % respectively for electricity consumption and construction materials overall. In the other hand, comparing both electricity consumption and construction materials, it is found that during operation at KICT building generate four (4) times more carbon dioxide than embodied carbon from construction materials. A general conclusion is that Malaysian construction industry needs to work towards sustainable consumption in the construction projects. One key factor to success is to work in cross function teams where different knowledge and experience cooperate and make the emission reduction even more efficient. Also, regulatory information from manufactures and experts are necessary as well as information about emissions related to current and new technologies and materials.